Visualization of Coalescence of Multiple Small Bubbles with Closed B-Spline Curve. (27th August 2020) - Zhang, Fangfang; Li, Hongjun
Abstract : The smoothness of surface shape is one of the key issues to simulate coalescence of underwater bubbles. In this paper, B-spline closed curve is used to realize the visual simulation of multibubble coalescence. The main idea of the proposed algorithm is to construct a continuous bubble deformation which is guided by the normal direction of each control point and weighted by the distance from the point to the geometry center of the contour. The advantages of this algorithm include the smoothness of the bubble contour in the processing of deformation and the randomness of dynamic process and coalescence process. Experiment results show that the simulation algorithm works well and can be used in 3D computer games and animations.